GTPBP2 in-frame deletion in canine model with non-syndromic progressive retinal atrophy - Leonardo Murgiano; Jessica K Niggel; Eylem Emek Akyürek; Roberta Sacchetto; Gustavo D. Aguirre (Scientific Reports)
Abstract Progressive retinal atrophy (PRA), caused by aberrant functioning of rod/cone photoreceptors, leads to blindness affecting mammals, including dogs. We identified a litter of three Labrador retrievers affected by non-syndromic PRA; the parents and three other siblings were unaffected. Homozygosity mapping and whole-genome sequencing detected a homozygous 3-bp deletion in the coding region of GTPBP2, located in CFA12 (NC_049233.1:12,264,348_12,264,350del, c.1606_1608del, p.Ala536del). The variant was absent from the online European Variation Archive (EVA) database, the Dog Biomedical Variants Database Consortium, and the Dog10k database. We tested 91 non-affected dogs from the same kennel and found 75 wild-type (WT) and 16 carriers, all clinically normal, and 569 Labradors from the general population (USA), all WT. GTPBP2 is associated with Jaberi-Elahi syndrome (JES) in Homo sapiens, and splice variants in Mus musculus are associated with neurodegeneration; in both cases photoreceptor degeneration may be included in its manifestation. Heterologous cellular systems were transfected with cDNA encoding WT or A536del mutant GTPBP2 protein and immunoblot analysis of total cell lysate with anti-GTPBP2 antibodies showed that the expression level of the GTPBP2 mutant protein A536del is slightly but not significantly reduced compared to WT. Immunofluorescent methods and confocal analysis of cells transfected with WT or A536del GTPBP2 protein revealed that the WT form is diffuse throughout the cytosol, while the mutant form resulted in the formation of cytoplasmic aggregates in ~70–80% of cells. The deleted amino acid falls within a conserved interval outside the GTP domain of GTPBP2, suggesting a potentially novel role of the sequence on cellular localization of the protein.